Predictors of Long-Term Healing for Endorectal Advancement Flap for Anorectal Fistulas - Muharrem, Oner; Abbas, Maher Aref (Journal of Coloproctology, 2023)
Introduction Anorectal fistulas are some of the commonest surgical proctologic disorders treated by surgeons. Despite the recent introduction of various sphincter preserving techniques, the search for the optimal operation continues. The purpose of this study was to determine the predictors of long-term healing for the endorectal advancement flapMethods A retrospective review of a single surgeon experience with the endorectal advancement flap for anorectal fistulas over an 18-year period. The impact of various patient and fistula related factors were analyzed for their impact on the primary endpoint of long-term fistula healingResults 87 patients underwent endorectal advancement flap (Male/Female 42.5/57.5%). Median age was 41 years. Sixty-nine patients (79.3%) had anal fistula while 18 patients had rectal fistula (20.7%). An anterior based fistula was noted in 45 patients (51.7%). The most common etiology was cryptoglandular disease (87.4%). The median operative time was 75 minutes (range 36-250). Postoperative septic complications were noted in 4 patients (4.6%). Fistula healing was documented in 80 patients (93%). During a median follow-up of 4 months (range 1-38, 1 patient lost to follow-up), recurrence was noted in 8 patients (9.3%), yielding an overall long-term success rate of 83.7%. The long-term healing rate was higher in patients with fistulas from cryptoglandular etiology (86.6%) compared to fistulas from other etiologies (63.6%) [p = 0.027].Conclusions The endorectal advancement is associated with a high healing rate, a low postoperative septic complication rate, and infrequent risk for recurrence. Long-term healing without recurrence is achieved more frequently in patients with cryptoglandular etiology of the fistula compared to patients with non-cryptoglandular etiology.
Keywords: anorectal fistula; endorectal advancement flap; healing; predictor of outcome